Distributed UPS control systems reliability analysis. (November 2017) - Addabbo, Tommaso; Fort, Ada; Mugnaini, Marco; Vignoli, Valerio
Abstract: Modern power systems should comply with high reliability and availability standards in order to meet customer final expectations and market needs. In this context it is quite obvious that modern uninterruptible power supply (UPS) have started to exploit improvement strategies to achieve higher availability figures over time. At the same time, power, size and performance constraints become stricter placing tight barriers to developers. UPS developers started therefore to design distributed systems where different functions could be allocated to different control board sections. The newly designed systems resulted to have higher availability and improved modularity and expandability. In this paper the authors compare the availability performance of an UPS with a single core control board with a distributed UPS based on multiprocessor control boards. Additionally, a model for the variations of the failure rate due to environmental changes is proposed. In particular, Weibull probability density functions have been considered in order to take into account failure rate changes induced by temperature increase at warmup in a limited time frame.